Assessing Studentsâ Ethnicities and Critical Thinking Skill to Develop PBL Based-Biology Learning Tools - Boleng, Didimus Tanah; Lumowa, Sonja V.T.; Palenewen, Evie (Biosaintifika: Journal of Biology & Biology Education, 2018)
A survey has been conducted in grade XI natural science of senior high school, at odd semester, academic year 2016/2017 in Samarinda, Indonesia. The focus of this research are to determine the studentsâ ethnicities, and the responses of biology teachers about students critical thinking skills, and Problem-Based Learning. Sampling technique was total sampling. The research instrument was a questionnaire. Data was analysed by techniques used descriptive. The results of the data analysis show that the compositions of studentsâ ethnics are: Java (12.7%), Bugis (6.9%), Kutai (13.3%), Banjar (13.3%), and other ethnics (28.5%). Most of the teachers (86.0%) who already understood about the learning approaches, said that they already understood, while the remaining 14% did not understand the patterns of Problem-Based Learning. In addition, 23.3% teachers said that students were less able to explain, express opinions, and make conclusions; 76.7% said that students are sufficiently able to explain, express opinions, and make conclusions. Future research related to biology learning in multiethnic students needs to be conducted to get more information. The design of learning tools needs to consider the ethnic Â of the students in strengthening critical thinking skills. Similar research needs to be done to obtain more information.The findings of this research are the studentsâ ethnicities of the XI class of Natural Sciences, as well as the responses of high school biology teachers about students critical thinking skills in Biology.